La production d’une représentation touristique. Une objectivation des guides Lonely Planet sur le Groenland - Antoine Delmas (Belgeo, 2013)
This article uses Lonely planet books published about Greenland between 1991 and 2005 to do a diachronic study. The central theme of these books is the will of their authors to highlight close-knit communities specific of main readership, backpackers. Criticize other tourists should be a way to create a collective identity and a singular way to discover wilderness and culture, the most important attractions of the island. Nevertheless this collective identity can be questioned in comparison to previous study and fieldwork.